Adverse effects of treating bruxism and masseter muscle hypertrophy with botulinum toxin injection - a literature review - Ratyna, Klaudia; Bochenek, Oliwia; Koper, Mateusz; Kałuża, Jessica; Konaszczuk, Adrian; Nowak, Aleksandra; Kozyra, Oliwia; Szypuła, Zofia; Paluch, Katarzyna; Skarbek, Małgorzata (Quality in Sport, 2024)
Background Botulinum toxin injection in the masseter muscle has gained popularity for both therapeutic and aesthetic applications, such as treating bruxism, masseter hypertrophy and lower facial slimming. Despite its efficacy, adverse effects associated with this procedure have been documented. This literature review aims to analyse and summarize the adverse effects associated with botulinum toxin injection in the masseter muscle, examining their incidence, underlying mechanisms and management strategies. Keywords botulinum toxin, masseter hypertrophy, bruxism, complications, adverse effects Material and methods A comprehensive search of databases including PubMed, MEDLINE and Google Scholar was conducted using above-mentioned keywords. Conclusions Masseter muscle botox injection is considered a safe procedure with low incidence rate. Although the complications are temporary, they can significantly reduce patient satisfaction and confidence. To minimize the risk of complications, clinicians should familiarize themselves with risk mitigation strategies.